Medical Students’ Attitude towards Healthcare Technologies and Healthy Lifestyle (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the results of a sociological survey of students of medical institutes in the example of Bukhara State Medical Institute (BSMI) and Tashkent State Dental Institute (TSDI). The analysis of the students’ responses allowed to conclude that not all the students have an idea of healthcare technologies, there is no particular interest in issues of a healthy lifestyle (HLS). A certain pattern was revealed in the respondents’ answers, the motivation to lead a healthy lifestyle increases dynamically with the transition to subsequent courses of study. Apparently, this is due to the acquisition of relevant knowledge on valeology, hygiene and healtcare factors in clinical disciplines that students take in older courses of study.